2021
DOI: 10.3390/ma14226825
|View full text |Cite
|
Sign up to set email alerts
|

External Condensation of HFE 7000 and HFE 7100 Refrigerants in Shell and Tube Heat Exchangers

Abstract: The paper describes the results of experimental studies of media as an intermediary in heat exchange taking place in low volume conditions. Their properties predestine them both as a future-proof for transporting and storing heat materials. The paper concerns the current topic related to the miniaturization of cooling heat exchangers. There are many studies in the literature on the phase transition of refrigerants in the flow in pipe minichannels. However, there is a lack of studies devoted to the condensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The results of the authors' own research showed that the heat transfer in exchangers during the condensation of refrigerants was characterized by an increase in efficiency in relation to single-phase systems [36]. It is also known that the use of mixtures of MPCM and water as a coolant has a positive effect on the intensity of heat transfer in heating/cooling (thermal) devices.…”
Section: The Current State Of Knowledgementioning
confidence: 99%
See 4 more Smart Citations
“…The results of the authors' own research showed that the heat transfer in exchangers during the condensation of refrigerants was characterized by an increase in efficiency in relation to single-phase systems [36]. It is also known that the use of mixtures of MPCM and water as a coolant has a positive effect on the intensity of heat transfer in heating/cooling (thermal) devices.…”
Section: The Current State Of Knowledgementioning
confidence: 99%
“…MPCM slurry is presented in Figure 3. The physical and chemical properties of the HFE 7000 refrigerant are presented in [36], while the properties of the MPCM slurry, i.e., viscosity, density, heat conductivity, specific heat, and heat of fusion, as well as the procedure for their determination have been presented in a number of previous studies [38][39][40][41][42].…”
Section: Data Reductionmentioning
confidence: 99%
See 3 more Smart Citations